STRATEGI PENETAPAN HARGARESTORAN JEPANG HANAMASA DALAM MENCIPTAKAN PROSES KEPUTUSAN PEMBELIAN KONSUMEN : Survei pada Pengunjung Restoran Jepang Hanamasa Dago Bandung - Pujilestari Indriasar Suwandi, - (2009)
Pujilestari Indriasari Suwandi, 054182, The Influence of Pricing Strategy Towards Customers Decision Making Process (A Survey on Customers at Hanamasa Restaurant Dago Bandung). Under the guidance of Dr. Lili Adi Wibowo, S. Sos., S.Pd., MM. dan Any Ariani Noor S.Pd. MSc. Japanese Restaurant has increased rapidly through the high competition. Hanamasa Restaurant realized that customers become more selective in decision making because there's many Japanese restaurant with the similar concept. Because of that, Hanamasa Restaurant makes a pricyng strategy to make acustomers be more interest with them. Price is an important part of the marketing mix. In customers' decision making, price is also being an important factor. Hanamasa Restaurant maintains their strategy of price by make a price variation which is called a package price. Considering these phenomena, so that needs to make a research of "The Influence Of Pricing Strategy Towards Customers Decision Making Process". The object of this research is Hanamasa Restaurant Dago Bandung, used the theory of Armstrong dan Kotler 2007:278 which said that price strategy is a money that billing to a product or service, amount of value which is exchanged by the customers in order to get a benefit to have or used the product or services with the reference which is said that pricing strategy influenced the customers decision making process, according to Kotler (2002:518) which is said that "Price is the first factor when customers make a decission. This study employed descriptive method and explanatory survey with size of 100 samples. The data were collect through interviews, observations, questionnaires, and documentation. It utilized data analysis technique of Path Analysis. The result of the study showed that the pricing strategy which is cosist of discount and allowance pricing strategy, psychological pricing strategy, promotional pricing strategy and valuating pricing strategy present significant influence in costumers decision making process at Hanamasa Dago Bandung.